Sci/Comm Scholars: A Facilitated Peer-To-Peer Working Group for Integrating Rhetorical and Social Scientific Approaches for Inclusive Science Communication - King-Kostelac, Amelia; Gomez, Eres A.; Finucane, Mary M.; Gorton, Sarah; Killian, Jamie L.; Walker, Kenneth; Bush, Janis K.; Smith, Jennifer A. (Frontiers in Environmental Science, 2022)
Graduate students emerging from STEM programs face inequitable professional landscapes in which their ability to practice inclusive and effective science communication with interdisciplinary and public audiences is essential to their success. Yet these students are rarely offered the opportunity to learn and practice inclusive science communication in their graduate programs. Moreover, minoritized students rarely have the opportunity to validate their experiences among peers and develop professional sensibilities through research training. In this article, the authors offer the Science Communication (Sci/Comm) Scholar’s working group at The University of Texas at San Antonio as one model for training graduate students in human dimensions and inclusive science communication for effective public engagement in thesis projects and beyond. The faculty facilitated peer-to-peer working group encouraged participation by women who often face inequities in STEM workplaces. Early results indicate that team-based training in both the science and art of public engagement provides critical exposure to help students understand the methodological care needed for human dimensions research, and to facilitate narrative-based citizen science engagements. The authors demonstrate this through several brief profiles of environmental science graduate students’ thesis projects. Each case emphasizes the importance of research design for public engagement via quantitative surveys and narrative-based science communication interventions. Through a faculty facilitated peer-to-peer working group framework, research design and methodological care function as an integration point for social scientific and rhetorical training for inclusive science communication with diverse audiences.